Cannabis use and stigma among Canadian high school students: Results from the 2015 and 2017 Cancer Risk Assessment in Youth Survey. (December 2020) - Buttazzoni, Adrian; Tariq, Ulaina; Thompson-Haile, Audra; Burkhalter, Robin; Cooke, Martin; Minaker, Leia
Highlights: A pan-Canadian sample of teens from 2015 (n = 12, 110) and 2017 (n = 15, 191) analyzed. Logistic regression used to examine links between stigma markers and cannabis use. Race, maternal education, and living arrangements were significant correlates. Clinical strategies recommendations are discussed. Future research should explore cannabis initiation experiences in vulnerable groups. Abstract: Background: Adolescent cannabis use is perceived as a risky behavior, has been linked with many negative health outcomes, and is increasingly being connected with stigma. Methods: The purpose of this study is to investigate how cannabis use is associated with potentially stigmatizing markers of identity among adolescents two waves of a repeat cross-sectional survey (2015 N = 12, 110; 2017 N = 15, 191) of high schools students in seven Canadian provinces. Students were asked about ever use of cannabis, as well as "stigma markers", including their current living arrangement, mother's education, and ethnicity. Multivariable logistic regression models were used to examine associations between cannabis use and stigma markers. Results: After adjusting models for grade, gender, and province of residence, students who did not live with their mothers had higher odds of cannabis use relative to students living with their mothers [OR = 1.94, 95% CI 1.62–2.31]. Low maternal education was also significantly associated with cannabis use, as was ethnicity (students who identified as Indigenous had 3.38 (95% CI 2.29–4.99) times higher odds of using cannabis compared to students who identified as "white" in 2017). Findings related to attending school in a rural (vs. urban) area (2015 OR = 1.33 95% CI 0.99–1.78; 2017 OR = 1.44 95% CI 0.9 to −2.15) and low SES (2015 OR = 0.99, 95% 0.98–1.00; 2017 OR = 1.00, 95% CI 0.98–1.01) were more marginal. Conclusions: Future research should explore cannabis initiation experiences among vulnerable groups to better understand potential stigma triggers.